Aprendemos a clasificar las palabras según la ubicación del acento - Vega Leon, Magali Angelita (2019)
The next learning session entitled: “We learn to classify words according to the position of the accent” was designed for students of the first year “B” of secondary level of the I.E Antonio Torres Araujo. This session aims to ensure that these students are able to recognize the word classes according to the position of the accent, thus differentiating the “agudas, graves, esdrújulas and sobreesdrújulas” words. Therefore, in the future, they can apply it in the production of their written texts._x000D_ The teacher through the session guides and explains to the students what is an accent and what is the marking, presents and reminds the rules of accentuation and how to put a tilde over a word, presents the classification of the words according to the position of their accent and puts them in practice with words easy to understand by students. These elements will be addressed during the class session, reinforcing the understanding and appreciation of literature in general and improving spelling in students.